Uji Potensi Ekstrak Daun Nilam (Pogostemon cablin Benth.) Dalam Sediaan Salep Jerawat Untuk Menghambat Pertumbuhan Bakteri Cutibacterium acnes dan Staphylococcus aureus - Evha Astaviana MS; Ulfayani Mayasari; Rasyidah Rasyidah (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Introduction: Cutibacterium acnes and Staphylococcus aureus are Gram-positive bacteria that serve as the primary etiological agents in the pathogenesis of acne vulgaris. Bacterial resistance to conventional antibiotics and their associated side effects have driven the development of alternative therapies based on natural products. Patchouli leaves (Pogostemon cablin Benth.) are known to contain bioactive compounds with antibacterial potential; however, studies on the formulation of their topical preparations remain limited. Objective: This study aimed to evaluate the antibacterial activity of patchouli leaf extract in ointment formulations against C. acnes and S. aureus, as well as to characterize the physical quality of the resulting preparations. Methods: Patchouli leaf extraction was carried out using the maceration method with 96% ethanol as the solvent. Identification of chemical compounds was performed through phytochemical screening. Antibacterial activity testing of the extract and ointment preparations was conducted using the disc diffusion method against C. acnes and S. aureus at extract concentrations of 10%, 15%, 20%, 25%, and 30%. The ointment formulations were prepared using a PEG 400 and PEG 4000 base, followed by evaluation of their physical characteristics, including homogeneity, pH, spreadability, viscosity, adhesion, and irritation tests. Data were analyzed using one-way ANOVA followed by Duncan's post-hoc test (α = 0.05). Results: Phytochemical screening revealed that patchouli leaf extract contained flavonoids, alkaloids, terpenoids, steroids, tannins, and saponins. The inhibitory activity of the extract against both test bacteria increased with increasing concentration, with the highest inhibition zones observed at 30% concentration (19.85 mm against C. acnes and 19.23 mm against S. aureus). The ointment formulations at extract concentrations of 25% and 30% produced inhibition zones of 22.38 mm and 26.36 mm against C. acnes, and 24.10 mm and 27.46 mm against S. aureus, respectively. All physical quality parameters of the ointments (homogeneity, pH 5.96–6.41, spreadability 5 cm, viscosity 2,018–2,164 cps, adhesion 9–14 seconds) met the required standards and did not cause irritation. Conclusion: Patchouli leaf extract (P. cablin Benth.) ointment at concentrations of 25% and 30% demonstrated strong antibacterial activity against C. acnes and S. aureus, with physical characteristics that met quality standards. These findings indicate the potential development of patchouli leaf extract ointment as a natural topical alternative therapy for acne vulgaris.